The collaborative innovation bloc: A reply to our commentators - Niklas Elert; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2019)
We are grateful for the comments to our article, and for the opportunity to respond to them. In our original contribution, we argued that the application of the EOE perspective could help make Austrian economics more concrete, relevant and persuasive, especially regarding policy prescriptions. At the heart of this perspective is the idea that entrepreneurship, when construed as the act of building an innovative firm, is an inherently collaborative activity. The comments have strengthened our conviction that the EOE perspective is of value for Austrian economics and been of great help in furthering our thinking on the matter. The comments have also helped us see how the perspective fits in with the broader tradition of Austrian economics.
Keywords: B53; D20; G32; L23; L26; O33; 330; Austrian economics; Entrepreneurship; Innovation; Institutions; Schumpeterian entrepreneurship; Spontaneous order